2020
DOI: 10.1177/1359105320980793
|View full text |Cite
|
Sign up to set email alerts
|

Prevention for oneself or others? Psychological and social factors that explain social distancing during the COVID-19 pandemic

Abstract: Identifying the underlying psychological and social factors of social distancing is crucial to foster preventive behavior during a pandemic effectively. We investigated the relative contribution of self-focused factors (fear of infection, fear of punishment) and other-focused factors (moral judgment, moral identity, empathy for unspecific others, empathy for loved ones) in an online study in Germany ( N = 246) while COVID-19 was climaxing. Importantly, other-oriented factors were related to social distancing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 56 publications
3
41
0
1
Order By: Relevance
“…Caring for both self- and collective interest is supposed to be a fundamental human motive (e.g., Fehr and Fischbacher, 2003 ). This notion is supported by some empirical literature in which empathy is related to COVID-19 prevention behaviors ( Christner et al, in press ; Lunn et al, 2020 ; Pfattheicher et al, 2020 ). Thus, exposure to social relation cues may have activated empathy toward others, leading individuals to engage in collective-interested behavior (i.e., prevention behavior) during the COVID-19 pandemic.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Caring for both self- and collective interest is supposed to be a fundamental human motive (e.g., Fehr and Fischbacher, 2003 ). This notion is supported by some empirical literature in which empathy is related to COVID-19 prevention behaviors ( Christner et al, in press ; Lunn et al, 2020 ; Pfattheicher et al, 2020 ). Thus, exposure to social relation cues may have activated empathy toward others, leading individuals to engage in collective-interested behavior (i.e., prevention behavior) during the COVID-19 pandemic.…”
Section: Introductionsupporting
confidence: 62%
“…Therefore, prevention behavior can be regarded as prosocial behavior. Given that empathy is associated with prosocial behavior and cooperation (e.g., Eisenberg and Miller, 1987 ), it may indeed lead to prevention behaviors as already suggested by some researchers ( Christner et al, in press ; Lunn et al, 2020 ; Pfattheicher et al, 2020 ). Sakakibara and Ozono (2020) provided suggestive findings with respect to the psychological factors that promote prevention behaviors via a survey conducted from the end of April to the beginning of May with a Japanese sample 8 .…”
Section: Discussionmentioning
confidence: 71%
“…Some works tested messages highlighting consequences on close others, or kinship. Christner et al (2020) found that moral judgments and empathy for loved ones are associated with intentions to practise social distancing, beyond self-oriented factors.…”
Section: Social Distancingmentioning
confidence: 96%
“…Practically, the current research suggests a cultural dynamic perspective to interpret crosscultural differences on compliance with COVID-19-related mitigation measures. Jordan and colleagues (2020) found evidence supporting that emphasizing prosocial (interdependent) than proself (independent) benefits is more effective in stimulating COVID-19 prevention intentions within Western countries (see also Christner et al, 2020). And Lu and colleagues (2021) found that cultural collectivism (vs. individualism), both within the United States and across the world, predicts mask usage after controlling for other political and socio-economic predictors.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%